2010
DOI: 10.1007/s12011-010-8691-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Supplementation on the Status of Thyroid Hormones and Na, K, and Ca Levels in Blood Following Ethanol Feeding

Abstract: The influence of zinc (Zn) on the serum levels of triiodothyronine (T(3)), thyroxine (T(4)), thyroid-stimulating hormone (TSH) and sodium (Na), potassium (K), and calcium (Ca) was evaluated following ethanol toxicity to the rats. To achieve this, male Wistar rats (150-195 g) were given 3 ml of 30% ethanol orally, and zinc was given in the form of zinc sulfate (227 mg/l) in their drinking water daily for 8 weeks. Ethanol feeding resulted in a slight decrease in T(3) and T(4) levels and a significant increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The significant effect of nZnO at 30 mg/kg on serum growth hormone demonstrated in our study was in agreement with the result of Li et al [30] who reported that serum growth hormone level of piglets was elevated in the nano-Zn group than in the other groups. Meanwhile, no significant differences were found among treated groups in respect to serum TSH concentration, which is consistent with the previous report [36]. In contrast, Baweja et al [37] demonstrated that the levels of TSH were elevated after 8-weeks of zinc supplementation in female Westar rats.…”
Section: Discussionsupporting
confidence: 91%
“…The significant effect of nZnO at 30 mg/kg on serum growth hormone demonstrated in our study was in agreement with the result of Li et al [30] who reported that serum growth hormone level of piglets was elevated in the nano-Zn group than in the other groups. Meanwhile, no significant differences were found among treated groups in respect to serum TSH concentration, which is consistent with the previous report [36]. In contrast, Baweja et al [37] demonstrated that the levels of TSH were elevated after 8-weeks of zinc supplementation in female Westar rats.…”
Section: Discussionsupporting
confidence: 91%
“…These experimental studies are expected to improve the clinicians' knowledge about the main supplements being used, in order to clarify the potential risks or side effects and support patients in their use. zinc modulation thyroid function [36][37][38][92][93][94][95][96] inositol involvement in the intracellular TSH signaling, via PIP-3 inositol supplementation decreased circulating T3 and FT3 concentrations thyroid diagnostic oncometabolite the treatment, in combination with seleno-methionine, declined the elevated levels of TSH in patients with AIT and subclinical hypothyroidism immune-modulatory effect of myo-inositol in association with seleno-methionine in patients with euthyroid AIT beneficial effects of myo-inositol, seleno-methionine or their combination on PBMC exposed in vitro to H2O2-induced oxidative stress in both control and women with HT protective effect of myo-inositol on thyroid cells myo-inositol, either alone or in association with T3 improved cardiac lipid content and function of streptozocin-induced diabetic rats Funding: This research received no external funding.…”
Section: Discussionmentioning
confidence: 99%
“…In adult male rats, thyroid function has been slightly damaged by the oral administration of 3 mL 30% ethanol [92]. The moderate decrease in serum T3 and T4 and increase in serum TSH was reversed by the 8-week administration of zinc (Zinc sulfate, 227 mL in the drinking water).…”
Section: Zincmentioning
confidence: 99%
“…In humans, zinc supplementation brought the thyroid function back to normality in hypothyroidean patients. The majority of studies on zinc and the HT were focused on zinc supplementation, but these findings were not considered due to being out of the study aim [64,65,66].…”
Section: Discussionmentioning
confidence: 99%